STRATEGI PEMERINTAH DAERAH DALAM MEWUJUDKAN PENGENTASAN KEMISKINAN INKLUSIF - Samunawardi, Muhamad; Riansyah, Riansyah; Samring, Firmansyah (JURNAL ILMIAH DETUBUYA, 2024)
This study aims to analyze the strategy of the West Nusa Tenggara Regional Government in realizing inclusive poverty alleviation through a qualitative approach based on the Systematic Literature Review (SLR). This study reviews scientific literature from the Dimensions and Scopus databases in the period 2015–2024, with strict selection criteria to ensure data relevance and quality. The findings show that although various studies have discussed social assistance innovation, collaborative governance, and the role of local governments, there are still gaps in the overall integration strategy. This study finds that the success of an inclusive poverty alleviation strategy is highly dependent on the synergy between policy, technology, and community participation. Data visualization through VOSviewer reveals a close relationship between institutional aspects, digitalization services, and empowerment communities in driving equitable economic transformation. The results of this study recommend strengthening regional policies based on collaborative ecosystems and placing women's and children's issues in structural development priorities. Thus, this study contributes to the formulation of a more adaptive, participatory, and sustainable poverty alleviation strategy in a region with social complexity such as NTB.